The president is missing : a novel - Clinton, Bill, 1946-; Patterson, James, 1947- (Little, Brown and Company, Alfred A. Knopf, 2018)
As enemies plan an unprecedented attack on American soil, Washington is gripped by uncertainty and fear as rumors spread of a traitor in the cabinet and the president himself comes under suspicion, before he goes missing.